Ciclos políticos nos municipios brasileiros: interação entre o governo municipal e as demais esferas de governo através das transferências voluntárias - Vieira, Fausto José Araújo (2007)
This paper analyses the interaction between the mayor and other parts of the National Executive through the analysis of the discretionary transfers and the implications on public sector fiscal accounts. The use of discretionary transfers as political instrument is clearly perceived; there is a revenue increase in both municipal and also state/presidential election years. The impact of these discretionary transfers is significant to explain the difference among the expenditures, investment and social expenses. Therefore, as a counterpart, the municipal government increases its expenses by the end of its mandate as well as in the midst of it. Estimations suggest that expenses are statistically higher when there is a state and presidential election years rather than the mayor election period. Nevertheless, the results of the Municipal revenues show a different behavior compared to the expenses. The discretionary transfers usually do not explain the differences of the municipal collection. There is not a reduction of the municipal taxes collection in state and presidential election years, but the opposite occurs when there is mayor election. The outcome shows there is a cycle for the expenses both in the end and in the midst of the mandate, but there is a priority given to the revenue when it is a municipal election. A not balanced Panel will be used for all towns and cities of Brazil, where there were information found, by the period of 1996-2004.